Searching for New Targets and Treatments in the Battle Against Squamous Cell Carcinoma of the Head and Neck, with Specific Focus on Tumours of the Tongue - Sgaramella, Nicola; Gu, Xiaolian; Boldrup, Linda; Coates, Philip J; Fahraeus, Robin; Califano, Luigi; Tartaro, Gianpaolo; Colella, Giuseppe; Spaak, Lena Norberg; Strom, Adrian; Wilms, Torben; Muzio, Lorenzo Lo; et al. (Current topics in medicinal chemistry, 2018)
Squamous cell carcinoma of the head and neck, SCCHN, is a heterogeneous group of tumours not only concerning the site of origin but also regarding aetiology. The 5-year survival for the whole group of SCCHN tumours has not significantly improved over the last 20-25 years. Apart from tumour spread to lymph nodes, N status, gains and losses of specific chromosomes are the only factors shown to be independent prognostic markers for these tumours. Worldwide, an increasing number of people ≤ 40 years are seen being affected by tongue SCC, the most common tumour within the SCCHN group. Even without any clinical signs of metastasis, up to 30% of all tongue SCC have histologically detectable spread to lymph nodes. In this mini review, field cancerization, tumour microenvironment, the so called EMT (epithelial mesenchymal transition) process and the role of viruses in development of SCCHN are discussed as well as potential new therapeutic targets. For the group of tongue SCC, with the increasing incidence seen in young patients and particularly women, new data with impact on prognosis and treatment are urgently needed. But as long as data from the analyses of several sub sites are presented as valid for the whole group of tumours, this vital point is missed.
Keywords: Microbial Sensitivity Tests; Drug Screening Assays, Antitumor; Tongue; Humans; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; miRNA; Antineoplastic Agents; mikrobiální testy citlivosti; lidé; virus Epsteinův-Barrové; EBV; nádory hlavy a krku; Head and Neck Neoplasms; Papillomaviridae; Herpesvirus 4, Human; antivirové látky; nádory jazyka; Therapy; p63.; Squamous cell carcinoma; Tumor Microenvironment; Antiviral Agents; screeningové testy protinádorových léčiv; Tongue Neoplasms; protinádorové látky; nádorové mikroprostředí; spinocelulární karcinom; Carcinoma, Squamous Cell; HPV; Prognosis